ANALYSIS OF FINANCIAL RISK MANAGEMENT IMPLEMENTATION FOR OPERATIONAL COST EFFICIENCY AT PARAMEDIKA BEKASI HOSPITAL - Wendy Mochamad Ramdhan; Erliany Syaodih; Budi Santoso (RADJA PUBLIKA, 2026)
This study aims to analyze the implementation of financial risk management and its impact on the efficiency of operational costs at Paramedika Bekasi Hospital. The research employs the SNI ISO 31000:2018 framework as the analytical foundation. The method applied is a descriptive qualitative case study. Data were collected through in-depth interviews with key informants, documentation studies of financial reports, and field observations. The findings reveal that the implementation of financial risk management in the hospital does not meet the principles of SNI ISO 31000:2018. The process is reactive and fragmented, characterized by top-down communication, the absence of formal risk context establishment, undocumented risk assessment, treatment strategies reliant on internal borrowing, and ineffective monitoring mechanisms. This condition leads to the organization's inability to anticipate and mitigate various financial risks, which ultimately directly impacts the low efficiency of operational costs. The novelty of this research lies in its holistic approach, which integrates an international standard framework with an in-depth analysis of the unique context of private hospitals in Indonesia, particularly in an acute financial crisis situation.